2005
DOI: 10.1016/j.palaeo.2005.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene–Holocene radiolarian paleotemperatures in the Norwegian Sea based on artificial neural networks

Abstract: Artificial Neural Networks (ANN) were trained by using an extensive radiolarian census dataset from the Nordic (Greenland, Norwegian, and Iceland) Seas. The regressions between observed and predicted Summer Sea Temperature (SST) indicate that lower error margins and better correlation coefficients are obtained for 100 m (SST 100 ) compared to 10 m (SST 10 ) water depth, and by using a subset of species instead of all species. The trained ANNs were subsequently applied to radiolarian data from two Norwegian Sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 61 publications
1
17
0
1
Order By: Relevance
“…between 8.5 and 5.5 ka BP) at the Vøring Plateau. Moreover, at the same site, SST reconstructions based on foraminifera and radiolarians also lack this early HTM suggested by diatoms (Risebrobakken et al, 2003(Risebrobakken et al, , 2011Cortese et al, 2005;Dolven et al, 2002). Jansen et al (2008) suggest that the SST maximum recorded in proxy data above the seasonal thermocline (diatoms, alkenones) is forced by the summer insolation maximum and that deeper dwelling species (foraminifera and radiolarians) are not influenced.…”
Section: Introductionmentioning
confidence: 80%
“…between 8.5 and 5.5 ka BP) at the Vøring Plateau. Moreover, at the same site, SST reconstructions based on foraminifera and radiolarians also lack this early HTM suggested by diatoms (Risebrobakken et al, 2003(Risebrobakken et al, , 2011Cortese et al, 2005;Dolven et al, 2002). Jansen et al (2008) suggest that the SST maximum recorded in proxy data above the seasonal thermocline (diatoms, alkenones) is forced by the summer insolation maximum and that deeper dwelling species (foraminifera and radiolarians) are not influenced.…”
Section: Introductionmentioning
confidence: 80%
“…The most accurate data were produced by the NGO. Cortese et al (2005) found, based on three test runs, that the NGO generated slightly lower error rates than the iModel.…”
Section: Methodsmentioning
confidence: 94%
“…The network output is compared to the assumed output, which is specified by the computer simulation (as supervisor), and the error for all the neurons in the output layer is calculated. The essential mechanism behind back propagation is that the error is propagated backward to earlier layers so that a gradient descent algorithm can be applied (Malmgren, Nordlund 1997;Malmgren et al 2001;Cortese et al 2005;Kucera et al 2005).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations